THE CURRENT SCREENING TECHNOLOGIES OF GENE EXPRESSION PROFILE IN DIABETES MELLITUS - Asmara, Holifa Saheera; Haque, Mainul (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Diabetes is commonly observed as a complexity and alteration of metabolic pathways through the oxidative stress and inflammations. It is a chronic condition, which has shown adverse effects and damages mechanisms. A broad study involving latest technologies has been conducted to view the alteration of gene expressions in order to understand the underlying of diabetes complications, a high rank of mortal disease worldwide, which demands a high cost of treatments and medications. Current technology has engaged with the method of gene expression detection, which is available in the laboratory settings, includes microarray system, real-time PCR (RT-PCR) and next gene sequencing (NGS). The output from gene expressions studies contributes to a better understanding of the molecular mechanism, promising a better possible gene target therapy and preventions.